Sebaceous hyperplasia of the nasal mucosa in a newborn. - Garofalo, L. (European Journal of Pediatric Dermatology, 2016)
A search in PubMed by typing “sebaceous gland and nasal mucosa” did not unveil any similar case. The sebaceous hyperplasia of the newborn, secondary to the influence of maternal hormones on the production of androgens, is a common finding that is evidenced in about half of the newborns. The sebaceous glands appear as punctate, yellowish micropapules regularly distributed especially on the tip of the nose, where they are more obvious, but also on the cheeks, forehead, on the upper trunk and especially on the mammary areola, genitals and limbs. Ectopic sebaceous glands can also be found in the oral mucosa or the cervix (2). As in the current case, the hypertrophic sebaceous glands are associated with milia (1). We assume that in our case the collected sebaceous material derived from ectopic isolated sebaceous glands of the nasal mucosa nearer to the nasal orifice skin.